2016
DOI: 10.1017/ice.2016.292
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Risk Score for Prediction of Extended-Spectrum β-Lactamase–Producing Enterobacteriaceae in Bloodstream Isolates

Abstract: OBJECTIVE To develop a risk score to predict probability of bloodstream infections (BSIs) due to extended-spectrum β-lactamase-producing Enterobacteriaceae (ESBLE). DESIGN Retrospective case-control study. SETTING Two large community hospitals. PATIENTS Hospitalized adults with Enterobacteriaceae BSI between January 1, 2010, and June 30, 2015. METHODS Multivariate logistic regression was used to identify independent risk factors for ESBLE BSI. Point allocation in extended-spectrum β-lactamase prediction score … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
87
1
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 71 publications
(95 citation statements)
references
References 33 publications
6
87
1
1
Order By: Relevance
“…The current study also identified prior β‐lactam use and higher BSIMRS as independent predictors of empirical carbapenem therapy. Prior use of β‐lactams has been consistently demonstrated as a risk factor for infections due to ESBLE . High BSIMRS reflects guarded prognosis at initial presentation, which may lower the threshold to initiate empirical carbapenem therapy in patients with minor risk factors for ESBLE infections .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The current study also identified prior β‐lactam use and higher BSIMRS as independent predictors of empirical carbapenem therapy. Prior use of β‐lactams has been consistently demonstrated as a risk factor for infections due to ESBLE . High BSIMRS reflects guarded prognosis at initial presentation, which may lower the threshold to initiate empirical carbapenem therapy in patients with minor risk factors for ESBLE infections .…”
Section: Discussionmentioning
confidence: 99%
“…Because penicillin allergy is more frequently reported in elderly women, patients with penicillin allergy in this study were matched to those without penicillin allergy based on age (±10 years) and sex . Matching by site of acquisition was applied because extended‐spectrum β‐lactamase–producing Enterobacteriaceae (ESBLE) and P. aeruginosa are relatively more common in health care–associated than in community‐acquired BSI . Finally, to allow examination of the impact of antimicrobial stewardship interventions on carbapenem utilization, matching by time period before (January 1, 2010, to December 31, 2013) and after (January 1, 2014, to June 30, 2015) full implementation of antimicrobial stewardship interventions was performed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations